Clinical Gastroenterology 2021
DOI: 10.1136/gutjnl-2021-iddf.164
|View full text |Cite
|
Sign up to set email alerts
|

IDDF2021-ABS-0171 Long term outcomes of palliative colonic stent placement in malignant colonic obstruction: experience from a tertiary care oncology center in India

Abstract: within endoscopic reach, both > 2 cm in diameter & > 5 cm in length. There were no deaths due to FB ingestion. Conclusions This is the largest study of Endoscopic FB removal from Western India. This study showed that the majority of the FB were ingested by children. Even those with injury to the bowel were asymptomatic. Since the size of FB did not determine it being within the reach of the endoscope and Groups S, NS & C FBs are associated with injury to the bowel; we propose an attempt at removal should be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…9 Sundaram et al reported that colonic self-expanding metal stent achieves good palliation of malignant colonic obstruction in patients. 10 Katrevula et al determined potential role of optical diagnosis using endocytoscopy and endocytoscopy-computer-aided diagnosis to predict histopathological diagnosis of neoplastic diagnosis. 11 Another retrospective study from a tertiary care center reported a large number of children undergoing successful endoscopic retrieval of ingested foreign bodies.…”
mentioning
confidence: 99%
“…9 Sundaram et al reported that colonic self-expanding metal stent achieves good palliation of malignant colonic obstruction in patients. 10 Katrevula et al determined potential role of optical diagnosis using endocytoscopy and endocytoscopy-computer-aided diagnosis to predict histopathological diagnosis of neoplastic diagnosis. 11 Another retrospective study from a tertiary care center reported a large number of children undergoing successful endoscopic retrieval of ingested foreign bodies.…”
mentioning
confidence: 99%